Study on the river sand removal capacity: case study at Bota Kiri, Sungai Perak - Sumayyah Aimi Mohd Najib (Tanjong Malim, 2019)
Study on the river sand removal capacity: case study at Bota Kiri, Sungai Perak by Sumayyah Aimi Mohd Najib